2017
DOI: 10.18632/oncotarget.20613
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling promotes aging-associated hair graying in mice

Abstract: Canities is an obvious sign of aging in mouse and human, shown as hair graying. Melanocytes in the hair follicle show cyclic activity with hair cycling, which transitions from anagen, catagen to telogen. How the hairs turn gray during aging is not completely uncovered. Here, by using immunostaining and LacZ staining in Dct-LacZ mice, we show that β-catenin is expressed in melanocytes during hair cycling. RT-PCR, western blot and immunostaining show that β-catenin expression is significantly increased in both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…) and is implicated in promoting melanocyte differentiation (Zhang et al . ). The Hippo pathway plays several prominent functions including regulation of homeostasis under oxidative stress and DNA damage response (Mao et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…) and is implicated in promoting melanocyte differentiation (Zhang et al . ). The Hippo pathway plays several prominent functions including regulation of homeostasis under oxidative stress and DNA damage response (Mao et al .…”
Section: Resultsmentioning
confidence: 97%
“…), and in promoting melanocyte differentiation (Zhang et al . ). Again, removal of this gene has led to diminished size of the appendicular skeleton in mice (Bandyopadhyay et al .…”
Section: Resultsmentioning
confidence: 97%
“…One mouse study found that β-catenin expression is significantly elevated in the skin of aged mice through WNT10b/β-catenin signaling promoting melanocyte stem cell differentiation. The authors concluded that the increase in WNT signaling is insufficient to induce hair regeneration but may promote melanocyte stem cell differentiation resulting in a decreased number of melanocyte stem cells and eventually hair graying [55].…”
Section: Wnt Signaling In Agingmentioning
confidence: 99%
“…Loss of the key signalling molecules (eg, Bcl2) that maintain the survival of McSCs causes the deletion of McSCs and hair greying . Forced activation or increased expression of Wnt signalling in McSCs induces exhaustion of McSCs and premature hair greying; TGF‐β type 2 receptor deficiency in hair follicle bulge causes incomplete maintenance of McSC quiescence, leading to mild hair greying in mice …”
Section: Hypopigmentation Looking Into the Relation Between The Clinmentioning
confidence: 99%